The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1010428320938492
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chilean patients with sporadic colorectal cancer according to the three main carcinogenic pathways: Microsatellite instability, CpG island methylator phenotype and Chromosomal instability

Abstract: Molecular classification of colorectal cancer is difficult to implement in clinical settings where hundreds of genes are involved, and resources are limited. This study aims to characterize the molecular subtypes of patients with sporadic colorectal cancer based on the three main carcinogenic pathways microsatellite instability (MSI), CpG island methylator phenotype (CIMP), and chromosomal instability (CIN) in a Chilean population. Although several reports have characterized colorectal cancer, most do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
(109 reference statements)
2
5
0
4
Order By: Relevance
“…Next, we analyzed the associations between the location and other kinds of molecular subtype including microsatellite instability (MSI), chromosomal instability (CIN), and CpG island methylator phenotype (CIMP) which are classified based on their distinct genomic and molecular characteristics. Consistent with existing study ( 26 ), we also found that RCC group has a higher proportion of MSI-H and a lower proportion of CIN patients compared to LCC group ( Figures S2A, B and Table 1 ). As for CIMP, we determined the CIMP subtype for each patient using the β value of DNA methylation panel or 7 methylation-related genes respectively.…”
Section: Resultssupporting
confidence: 92%
“…Next, we analyzed the associations between the location and other kinds of molecular subtype including microsatellite instability (MSI), chromosomal instability (CIN), and CpG island methylator phenotype (CIMP) which are classified based on their distinct genomic and molecular characteristics. Consistent with existing study ( 26 ), we also found that RCC group has a higher proportion of MSI-H and a lower proportion of CIN patients compared to LCC group ( Figures S2A, B and Table 1 ). As for CIMP, we determined the CIMP subtype for each patient using the β value of DNA methylation panel or 7 methylation-related genes respectively.…”
Section: Resultssupporting
confidence: 92%
“…Por otra parte, en las 12 muestras de cáncer colorrectal positivo para inestabilidad microsatelital, no se detectó la mutación V600E del gen BRAF; este resultado difiere de lo reportado en otros estudios en los que se informa que esta es más frecuente en muestras de cáncer colorrectal con MSI-H (16,19,22,30,43,44). En el presente estudio, cinco de las 12 muestras con inestabilidad microsatelital tenían MSI-H, por lo que el bajo número de muestras podría explicar que no se haya identificado esta mutación.…”
Section: Discussionunclassified
“…Sin embargo, nuestros resultados concuerdan con los publicados por otros autores que no encontraron esta relación en pacientes con cáncer colorrectal esporádico (45,46). En sentido contrario a la ausencia de mutaciones en el gen BRAF, en este estudio se encontró que el 16 % de los tumores positivos para inestabilidad microsatelital tenía mutaciones en el KRAS, siendo la mutación G12D la más frecuente, lo cual coincide con lo reportado por otros estudios (16,19,22,30,42,43,47). En general, nuestros hallazgos nos permiten sugerir que, en los casos de cáncer colorrectal esporádico, los positivos para inestabilidad microsatelital constituyen un subgrupo molecular que se caracteriza por presentar una baja frecuencia de mutaciones en los genes APC, KRAS, BRAF y TP53; en tanto que los pacientes con estabilidad microsatelital se caracterizan por presentar una mayor frecuencia de mutaciones en los genes analizados.…”
Section: Discussionunclassified
See 2 more Smart Citations